Analyzing the Effect of Liquidity and Solvency Ratios on Profitability at Pt Astra International Tbk (2015–2023) - Maghfirah Sultan, Nurul; Sahabuddin, Romansyah; Nurman; Amin, Andi Mustika; Aslam, Annisa Paramaswary (Bulletin of Management and Business, 2024)
This study investigates the impact of liquidity, as represented by the Current Ratio (CR), and solvency, as measured by the Debt to Asset Ratio (DAR), on profitability, proxied by Return on Assets (ROA), in the case of PT Astra International Tbk during the 2015–2023 period. Employing a quantitative approach with a descriptive method, this research analyzes secondary data sourced from the company’s quarterly financial reports. Multiple linear regression analysis is used to examine both the individual and combined effects of liquidity and solvency on profitability. The findings reveal that CR has a negative and statistically significant effect on ROA, indicating that higher liquidity may correspond to lower profitability. This suggests that excessive current assets could reflect underutilized resources that are not optimally contributing to income generation. Similarly, DAR also demonstrates a negative and significant relationship with ROA, implying that higher reliance on debt may reduce profitability due to the burden of interest and other financial obligations. Collectively, liquidity and solvency are shown to significantly influence profitability. These results highlight the importance of maintaining a strategic balance between current assets and debt to achieve sustainable financial performance. This study is limited to a specific period and a single company within the automotive and diversified industry, which may affect the generalizability of the conclusions. Future research is encouraged to explore additional financial indicators or conduct comparative studies across sectors to enhance the breadth and Uapplicability of the findings